The Impact of Students’ Satisfaction with Online Education on Their Mental Health - Karimi, Mahsa (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to determine the effect of students’ satisfaction with online education on their mental health. Methodology: This study employed a descriptive correlational research design. The statistical population included all high school students in Tehran during the 2023–2024 academic year. A total of 250 students were selected using a multistage cluster sampling method. Data were collected using the Mental Health Scale (Goldberg, 1979) and the Students’ Satisfaction with Online Education Scale (Zaghiri, 2022). Data analysis was conducted using Pearson’s correlation test and multiple regression analysis with SPSS-V25 software. Findings: The results indicated that 62% of students scored high on mental health components, including anxiety, depression, social dysfunction, and insomnia. Additionally, the mean score of satisfaction with online learning was assessed at a moderate level. Statistical analyses revealed a significant relationship between the level of satisfaction with online education and mental health (r=-0.52, p<0.01). Conclusion: The findings of this study suggest that while online education offers advantages such as flexibility and easy access to educational resources, it may also contribute to increased psychological issues, such as anxiety and depression, among students. Therefore, it is essential to design and optimize online educational programs with consideration of students’ psychological needs to mitigate the negative effects of this form of education. Additionally, it is recommended that psychological interventions be implemented alongside online education to better preserve students’ mental health.